Learning Perl : making easy things easy and hard things possible - Schwartz, Randal L.
Learning Perl closely follows the popular introductory Perl course taught by the authors since 1991. This seventh edition covers recent changes to the language up to version 5.24. The book teaches the basics and shows how to write programs up to 128 lines long--roughly the size of 90% of Perl programs. Each chapter includes exercises. Topics include: Perl data and variable types; subroutines; file operations; regular expressions; string manipulation (including Unicode); lists and sorting; process management; smart matching; use of third-party modules.